Characterization of atmospheric total gaseous mercury at a remote high-elevation site (Col Margherita Observatory, 2543 m a.s.l.) in the Italian Alps. (15th February 2022) - Vardè, Massimiliano; Barbante, Carlo; Barbaro, Elena; Becherini, Francesca; Bonasoni, Paolo; Busetto, Maurizio; Calzolari, Francescopiero; Cozzi, Giulio; Cristofanelli, Paolo; Dallo, Federico; De Blasi, Fabrizio; Feltracco, Matteo; et al.
Abstract: The Col Margherita (MRG) Observatory is a high-altitude background station located in the Eastern Italian Alps. Its elevation and distance from major anthropogenic and natural sources make it ideal for monitoring baseline mercury levels and investigating its geochemical cycles. In this work, total gaseous mercury (TGM), ozone (O3 ) and meteorological variables were studied to investigate seasonal and diurnal variability of TGM measurements from March 2018 to May 2019. We found that the year-round mean TGM concentration was 1.8 times higher than the annual atmospheric mercury measurements previously reported during the GMOS project at the same measurement site. The seasonal variation of TGM was characterized by high values in spring and summer and lower values in winter. A systematic diel pattern of TGM was obtained, with low concentrations during the daytime and higher concentrations in the late evening. Spatial patterns and temporal changes in TGM, back-trajectories (BTs) and planetary boundary layer (PBL) analysis showed that total gaseous mercury levels were influenced by local meteorology, as well as regional and long-range transport of air masses. The lowest TGM concentrations in winter are associated with high wind speeds, low boundary layer height and cleaner air masses originating from the Western sector. Conversely, the highest TGM concentrations in spring and summer were attributed to polluted air masses passing over North-eastern and Continental Europe and were probably favoured by the higher PBL height. During the snow cover season, investigation of TGM peak events also demonstrated the potential influence of re-emission processes of previously reactive mercury deposition over snow surfaces. Graphical abstract: Image 1 Highlights: A one-year record mean TGM concentration at the MRG was higher than other long-term values observed in remote mountain sites. TGM was characterized by high values in spring and summer and lower values in winter. A diel trend of TGM was observed, with low concentrations in the daytime and higher concentrations in the late evening. TGM levels were influenced by local meteorology, as well as regional and long-range transport of air masses. Analysis of specific atmospheric mercury elevated events (AMEEs) was performed.